Measuring and enhancing the effectiveness of regional integration policies for resource and environmental carrying capacity - Danling Chen; Xinhai Lu; Chaozheng Zhang; Yunlei Zhang; Dongming Liao; Jia Li (Humanities & Social Sciences Communications)
Abstract Governments worldwide announced regional integration stimulus packages to stimulate economic growth, offering a unique opportunity to address issues related to resource and environmental carrying capacity (RECC). China’s efforts to enhance RECC within the strategy content of regional integration provided valuable insights for global strategies. Taking the Yangtze River Economic Belt (YREB) as an example, this study developed a theoretical framework and employed a double differences (DID) model, alongside a mediation effect technology, for excavating the policy outcomes and specific mechanisms of which regional integration influenced RECC. Additionally, we conceptualized RECC improvement as a collective shift in behavior, shaped by a combination of capacity, motivation, and policy instrument choices, employing fsQCA. The findings revealed that the regional integration policies in urban agglomeration zones had a significant beneficial impact on RECC, increasing it by approximately 0.016 units. This investigation presents a comprehensive approach for enhancing regional integration policy effectiveness, aimed at improving RECC. We underscored the necessity of unblocking the intermediary mechanisms including economic linkage, industrial restructuring, and technological advancements through which regional integration policies impact RECC. Furthermore, the study highlights the importance of tailored policy instrument mixes, anchored in the local economic realities, administrative capacities, and regional variations, rather than relying on the uniform application of supply, demand, and environmental policy actions.